2019
DOI: 10.3390/cancers11040531
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Selective Binder of αVβ3 Integrin Linked to the Tyrosine Kinase Inhibitor Sunitinib in Ovarian Carcinoma Preclinical Models

Abstract: Ovarian carcinoma, the most lethal gynecological cancer, is characterized by late diagnosis, with drug resistance limiting the efficacy of platinum-based therapy. Since some integrins are upregulated in cancer, including ovarian carcinoma, they represent a potential target for drug delivery. Receptor tyrosine kinases are also deregulated in cancer and their expression has been associated with drug resistance. Here, the antitumor effects of three conjugates possessing a selective binder of the extracellular por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Cyclic pentapeptides containing the RGD motif (cRGDfK) are used to improve the drug delivery and target selectivity of anti-cancer drugs [ 34 , 35 , 40 , 45 , 46 ]. Many studies have demonstrated the potential of RGD-containing peptides as vectors for delivering anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyclic pentapeptides containing the RGD motif (cRGDfK) are used to improve the drug delivery and target selectivity of anti-cancer drugs [ 34 , 35 , 40 , 45 , 46 ]. Many studies have demonstrated the potential of RGD-containing peptides as vectors for delivering anticancer agents.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, cyclic peptides have been actively studied recently as biochemical tools and therapeutic agents because of their excellent stability, high resistance to exogenous peptidases, and high affinity and selectivity for binding to target biomolecules [44]. Cyclic pentapeptides containing the RGD motif (cRGDfK) are used to improve the drug delivery and target selectivity of anti-cancer drugs [34,35,40,45,46]. Many studies have demonstrated the potential of RGD-containing peptides as vectors for delivering anticancer agents.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…This strategy resulted in one active compound (Fig. 3A) that inhibits the growth of drug-sensitive and -resistant cells in the micromolar range, reduces cell migration and invasive abilities, and presents an increased potency compared with sunitinib (107).…”
Section: Cadherins and Integrins As Targets For Cancer Therapymentioning
confidence: 99%
“…During this endeavor, a new peptidomimetic chemotype of general formula c [Amp(Sub)RGD] was discovered (Figure ), in which a 4‐aminoproline residue (Amp) was used as a beneficial conformational restrain scaffold when embedded within a cyclic RGD peptide. Several compounds of type 4 showed excellent binding competence and good selectivity toward α V β 3 integrin in both cell‐free and in‐cell assays, which were exploited as intelligent vectors to selectively drive attached chemotherapeutics and/or imaging probes to tumor cells and tissues both in vitro and in vivo . With this experience, we were able to appreciate how even small structural variations within a series of closely related ligands could heavily impact the biological response in terms of cell internalization and in vivo antitumor activity …”
Section: Introductionmentioning
confidence: 99%